2019
DOI: 10.1186/s12986-019-0371-6
|View full text |Cite
|
Sign up to set email alerts
|

Resveratrol attenuates endothelial oxidative injury by inducing autophagy via the activation of transcription factor EB

Abstract: Background Endothelial oxidative injury is a key event in the pathogenesis of atherosclerosis (AS). Resveratrol (RSV) attenuates the oxidative injury in human umbilical vein endothelial cells (HUVECs). Autophagy is critical for the RSV-induced protective effects. However, the exact underlying mechanisms haven’t been completely elucidated. Thus, we aimed to explore the role of autophagy of the anti-oxidation of RSV and the underlying mechanism in palmitic acid (PA)-stimulated HUVECs. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
37
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 61 publications
(38 citation statements)
references
References 49 publications
1
37
0
Order By: Relevance
“…Emerging evidence indicates that RESV attenuates endothelial oxidative injury in HUVECs by inducing autophagy [11,23]. Here, in the present study we found that blocking autophagy with 3-MA aggravated the apoptosis by upregulating caspase3 expression, while inducing autophagy with rapamycin relieved the apoptosis, indicating that autophagy confers the ability to protect endothelial cells from CSE-induced apoptosis.…”
Section: Discussionsupporting
confidence: 67%
“…Emerging evidence indicates that RESV attenuates endothelial oxidative injury in HUVECs by inducing autophagy [11,23]. Here, in the present study we found that blocking autophagy with 3-MA aggravated the apoptosis by upregulating caspase3 expression, while inducing autophagy with rapamycin relieved the apoptosis, indicating that autophagy confers the ability to protect endothelial cells from CSE-induced apoptosis.…”
Section: Discussionsupporting
confidence: 67%
“…Reducing the ischemia-reperfusion injury-induced oxidative stress by inhibiting the activation of p38 MAPK pathway to increase antioxidants like GSH and scavenge free radicals [28] In vivo Rats 5, 10 mg/kg Activating SIRT1 to scavenge ROS [29] In vivo Mice 15, 30, 60 mg/kg Activating AMPK, SIRT1, and Nrf2 associated antioxidant defense pathways to improve systemic oxidative and nitrosative stress [30] In vivo Sows 300 mg/kg Regulating antioxidant gene expression via Keap1/Nrf2 pathway and SIRT1 [31] In vitro HUVECs 10 µM Inducing autophagy via the activation of TFEB [32] In vitro HEK293 cells or HEK293T 5 µg/mL Inducing autophagy via the AMPK-mediated inhibition of mTOR signaling [33] Anti-inflammatory activities…”
Section: µMmentioning
confidence: 99%
“…Autophagy is an essential intracellular process responsible for the selective degradation of pathogens, damaged organelles and proteins that cannot be degraded by the proteasome, to support protein and organellar homeostasis, as well as recycling of biomolecular resources, to maintain energy homeostasis and cell survival [23]. Emerging evidence indicates that RESV attenuates endothelial oxidative injury in HUVECs by inducing autophagy [13,24]. Here, in the present study we found that blocking autophagy with 3-MA aggravated the apoptosis by upregulating caspase3 expression, while inducing autophagy with rapamycin relieved the apoptosis, indicating that autophagy confers the ability to protect endothelial cells from CSE-induced apoptosis.…”
Section: Discussionmentioning
confidence: 99%